Interacting Roles of Executive Compensation on Organizational Slack and Firm’s Innovation Performance - Monika Pradnya Aurelia Wijayanti; Iman Harymawan; Nurul Fitriani (Jurnal Ilmiah Akuntansi dan Bisnis, 2024)
This study examines the interaction between executive compensation and three types of organizational slack (available, recoverable, and potential) and their impact on the innovation performance of publicly listed companies in Indonesia. The empirical analysis use a dataset of 1,081 firm-year observations from 2010 to 2019. The findings reveal that available slack positively affects innovation performance, whereas recoverable and potential slack have negative impacts. Executive compensation significantly moderates these relationships, especially nullifying the negative impact of recoverable slack on innovation. The results highlight the importance of strategic management and the role of executive compensation in enhancing a firm's innovation, offering valuable insights for shareholders and contributing to the understanding of organizational slack and compensation's effect on innovation in the Indonesian context.